Alarms, alerts, and warnings in air traffic control: An analysis of reports from the Aviation Safety Reporting System - Keith J Ruskin (Elsevier, 2021)
Signals (alarms, alerts, and warnings) are essential for alerting air traffic controllers to potential collisions and other adverse events. Excessive or misleading signals can increase response times and decrease their response rates. We used reports from the Aviation Safety Reporting System and structured interviews to understand the complexity of the controller’s tasks in the context of potentially high-consequence situations and events, and to develop design strategies to enhance the effectiveness of signals in the ATC environment. Methods: We reviewed ASRS reports over a 6-year interval from 2015 to 2020, searching for reports that mentioned alarm, alert, or warning and were submitted by air traffic controllers. We found 370 relevant reports that we analyzed for hits, misses, false alarms, and correct rejections. Structured interviews with former controllers further explored the role of signals in air traffic control. Results: The most common signals in reports were MSAW (139), ASDE-X and ASSC (27), CA (195), and AMASS (4). ASDE-X, ASSC, or AMASS were mentioned in 30 reports by ground or local controllers. TRACON controllers reported events involving MSAW 70 times and CA 51 times; these were also implicated by local controllers. CA was most mentioned, cited a total of 195 times in the reports. Conclusions: This information may help us to develop strategies that can enhance signaling modality (e.g., new auditory, visual, and tactile signals). Trust in automation may be improved by using strategies such as indicating the automation’s level of confidence in situations like impending loss of separation.